Comparison of Capital Market Reactions Before and After the Boycott of Products Due to War - Sukmawati SUKMAWATI; Prihat Assih; Edi Subiyantoro (University of Merdeka Malang, 2025)
The capital market is affected by economic and non-economic variables. Wars and political turmoil profoundly affect stock prices in the stock market due to their strong correlation with a nation's economic stability. Product boycotts can precipitate crises for corporations, resulting in diminished sales and thus affecting the stock price performance of the impacted firms. This study analyzes the variations in anomalous returns preceding and following the declaration of war-related product boycotts for targeted firms and their non-targeted rivals. This is quantitative descriptive research. The population comprises firms registered on the Indonesian Stock Exchange from 2023 to 2024. The sample included 37 companies, obtained purposive sampling and secondary data from Yahoo Finance.com. Event research analytical techniques were used in the investigation. The Wilcoxon signed-rank test for non-normally distributed data and the paired-sample t-test for regularly distributed data were among the statistical analyses used. The findings indicate a substantial disparity in anomalous returns for enterprises subjected to boycotts before and after the declaration of war-related product boycotts. No substantial difference in anomalous returns was seen for non-boycotted rival companies before and after the announcement of war-related product boycotts.